1938
DOI: 10.1136/bmj.2.4058.784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Blood Pictures in Adult Scurvy

Abstract: Cases of scurvy such as were described by clinicians in past generations are becoming very rare, and at the same time more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1942
1942
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The bone marrow has most often been described as normoblastic (Mettier et al 1930; McMillan and Inglis 1944; Vilter et al 1946; Brown 1951), but it may be megaloblastic as in the present case (Jennings and Glazebrook 1938; McMillan and Inglis 1944; Vilter et al 1946; R. Vilter 1947; Brontë‐Stewart 1953; Brown 1955; Neilson 1960; Will and Murdoch 1960), hyperplastic (Mettier et al 1930; Brontë‐Stewart 1953) or hypoplastic (Harris 1928; Wolbach 1937; Israëls 1943). Witts (1932) considered that vitamin C deficiency led to a maturation defect in the bone marrow.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The bone marrow has most often been described as normoblastic (Mettier et al 1930; McMillan and Inglis 1944; Vilter et al 1946; Brown 1951), but it may be megaloblastic as in the present case (Jennings and Glazebrook 1938; McMillan and Inglis 1944; Vilter et al 1946; R. Vilter 1947; Brontë‐Stewart 1953; Brown 1955; Neilson 1960; Will and Murdoch 1960), hyperplastic (Mettier et al 1930; Brontë‐Stewart 1953) or hypoplastic (Harris 1928; Wolbach 1937; Israëls 1943). Witts (1932) considered that vitamin C deficiency led to a maturation defect in the bone marrow.…”
Section: Discussionmentioning
confidence: 69%
“…Several workers have since shown that vitamin C deficiency without clinical scurvy is not associated with an increased incidence of anaemia (Croft and Snorf 1939; Lui, Chu, Yu, Hsu and Cheng 1941; Lozner 1941; Schulze and Morgan 1946; Vilter et al 1946). Nevertheless, cases of scurvy with anaemia which respond to the administration of vitamin C alone, with no other haemopoietic factor, continue to be described (Parsons and Hawksley 1933; Parsons and Smallwood 1935; Dunlop and Scarborough 1935; McFarlane 1936; Nisenson and Cohen 1937; Jennings and Glazebrook 1938; Parsons 1938; Young 1938; Kenney and Rapoport 1939; Braganca and Saha 1943; Vilter et al 1946; C. Vilter 1947; R. Vilter 1947; Brown 1951; Brontë‐Stewart 1953; Brown 1955; Neilson 1960; Will and Murdoch 1960; Cox et al 1962 and the present authors).…”
Section: Discussionmentioning
confidence: 99%
“…The marrow findings were also similar to those recorded by others. These earlier findings were: (a) a gelatinous mass with failure of erythropoiesis (1 case) (Harris, 1927-8); (b) moderate hyperplasia with scattered small groups of erythroblasts and no fibrosis (1 case) (Mettier et al, 1930); (c) one normal marrow, and one megaloblastic marrow associated with macrocytosis and achylia gastrica (Jennings and Glazebrook, 1938); and (d) one normal marrow and two showing diminished erythropoiesis (Israels, 1943). The change from a megaloblastic to a normoblastic type with only dietary replacements was interesting.…”
Section: Treatmentmentioning
confidence: 94%
“…In occasional cases there has been a rapid increase in the degree of anaemia despite increased reticulocytosis (Mettier et al, 1930;Jennings and Glazebrook, 1938;Vilter et al, 1946;Bronte Stewart, 1950;Brown, 1951).…”
Section: Commentmentioning
confidence: 99%